(untitled) (Cadernos de Filosofia Alemã: Crítica e Modernidade, 2020)
In his first publications, Axel Honneth makes a fruitful confrontation with Marx and Habermas and explains the tasks that would still have to be faced by those who seek to develop a critical social theory today. Taking this confrontation as central to his critical project, I will analyze here some texts written by Honneth in the 1980’s, in which he seeks to resume the concept of work in critical theory and, while trying to expand and to complement it, develops a method of negative reconstruction and approaches the recognition category. My aim is to show that Honneth’s recognition theory can be understood as an intersubjective reformulation of his initial project of developing an immanent critique of capitalism able to encompass the moral dimension of class struggles and to identify a potential for transformation based on social experiences of injustice.